2008
DOI: 10.1016/j.jjcc.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Association of low-density lipoprotein particle size and ratio of different lipoproteins and apolipoproteins with coronary heart disease

Abstract: Findings from the multivariate analysis, apoB, apoB/HDL-c, nonHDL-c, apoB/apoAI, and LDL particle size are potent indicators and useful for diagnosis of predisposed CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…However, contrary to our conclusion, Nansseu et al [ 18 ] found AIP may not be an independent factor impacting the risk of CVD through a cross-sectional study conducted among 108 postmenopausal women in Cameroon. At the same time, atherogenic lipoproteins that have been identified, the high apoliprotein B, low apolipoprotein A-1 and the high ratio of apoB: apoA1 also affect the formation and progression of coronary atherosclerosis [ 31 , 32 ]. In our study, we also find an increased ratio of apoB: apoA1 value was a highly significant risk factor of CAD independent of smoking, hypertension, and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to our conclusion, Nansseu et al [ 18 ] found AIP may not be an independent factor impacting the risk of CVD through a cross-sectional study conducted among 108 postmenopausal women in Cameroon. At the same time, atherogenic lipoproteins that have been identified, the high apoliprotein B, low apolipoprotein A-1 and the high ratio of apoB: apoA1 also affect the formation and progression of coronary atherosclerosis [ 31 , 32 ]. In our study, we also find an increased ratio of apoB: apoA1 value was a highly significant risk factor of CAD independent of smoking, hypertension, and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 There is currently a lack of specific treatment options for low HDL-C and elevated TG due to a lack of efficacy data. Lipid medications that specifically target TGs and HDL-C, such as fibrates and niacin, have demonstrated a reduction of CVD events in some trials but not in many others.…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez et al [ 8 ]) alarmingly found that two-thirds of the Hispanic US population studied exhibited some form of dyslipidemia, with the highest incidence above 40 years of age. The high-triglyceride/low HDL-C dyslipidemia profile, which is described as atherogenic and linked to the metabolic syndrome, is particularly prevalent in this group [ 3 , 8 10 ]. In Mexico, the prevalence of dyslipidemias is also very high: a study based on the Mexican National Health and Nutrition Survey (ENSANUT 2006) indicated that the prevalence of total cholesterol concentrations ≥200 mg/dl was 43.6%, and the figures for LDL cholesterol ≥130 mg/dl, HDL cholesterol <40 mg/dl and triglycerides ≥150 mg/dl were 46%, 60,5% and 31.5%, respectively [ 11 ].…”
Section: Introductionmentioning
confidence: 99%